ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU DALAM PELAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Property Yang Terdaftar Di BEI Tahun 2019-2021) - Fivian Imdadilluthfiyah; Moh. Amin; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to analyze profitability, liquidity, and firm size affect the timeliness of financial reporting. The population used in this study is the property of companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021. While the sample used in this study is purposive sampling. There are 83 companies that are included in the property sector but the sample that can be processed is 33 companies. The results of this study indicate that profitability and firm size affect timeliness in financial reporting, liquidity does not affect timeliness in financial reporting.Keywords: Profitability, liquidity, firm size, financial reporting timeliness.